An updated review of adhesively bonded joints in composite materials. (January 2017) - Budhe, S.; Banea, M.D.; de Barros, S.; da Silva, L.F.M.
Abstract: Continuing interest and more developments in recent years indicated that it would be useful to update Banea and da Silva paper entitled "Adhesively bonded joints in composite materials: an overview". This paper presents an updated review of adhesively bonded joints in composite materials, which covers articles published from 2009 to 2016. The main parameters that affect the performance of bonded joints such as surface treatment, joint configuration, geometric and material parameters, failure mode etc. are discussed. The environmental factors such as pre-bond moisture, moisture and temperature are also discussed in detail and how they affect the durability of adhesive joints. Lots of shortcomings were resolved during the last years by developing new materials, new methods and models. However, there is still a potential to evaluate and identify the best possible combination of parameters which would give the best performance of composite bonded joints.